Survival of an Escherichia coli in a Sarawak Soil - Ling, Teck Yee; Kasing, A.; Mijen, A.L. (Malaysian Society of Soil Science, 2002)
Soil is a natural digestion system for animal wastes. However, land disposal sites and agricultural land pose serious threats to the quality of surface and groundwater. In this study, a clay loam, Semongok series, from Sarawak was inoculated with wild strain E. coli isolated from animal wastes. Results indicated that first order decay rate increased as temperature increased from 25°C to 35°C and as moisture decreased from saturation to air-dry. Lag period of the bacteria was found to be the longest (8 days) in saturated soil at 25C and the shortest (l day) in air-dried soil at 35C. Interaction between temperature and moisture was significant. First order decay model can be used after lag period to estimate E. coli decay. The best data fit was obtained under cool wet condition. Temperature correction coefficient in the range of 25-35°C was 1.18. It is recommended that disposal of animal wastes be. carried out during hot dry seasons of the year.